Time limit and V̇O2 kinetics at maximal aerobic velocity: Continuous vs. intermittent swimming trials - Almeida, Tiago A. F.; Massini, Danilo A.; Silva Júnior, Osvaldo T.; Venditti Júnior, Rubens; Espada, Mário A. C.; Macedo, Anderson G.; Reis, Joana F.; Alves, Francisco B.; Pessôa Filho, Dalton M. (Frontiers in Physiology, 2022)
The time sustained during exercise with oxygen uptake (V̇O2) reaching maximal rates (V̇O2peak) or near peak responses (i.e., above second ventilatory threshold [t@VT2) or 90% V̇O2peak (t@90%V̇O2peak)] is recognized as the training pace required to enhance aerobic power and exercise tolerance in the severe domain (time-limit, tLim). This study compared physiological and performance indexes during continuous and intermittent trials at maximal aerobic velocity (MAV) to analyze each exercise schedule, supporting their roles in conditioning planning. Twenty-two well-trained swimmers completed a discontinuous incremental step-test for V̇O2peak, VT2, and MAV assessments. Two other tests were performed in randomized order, to compare continuous (CT) vs. intermittent trials (IT100) at MAV until exhaustion, to determine peak oxygen uptake (Peak-V̇O2) and V̇O2 kinetics (V̇O2K). Distance and time variables were registered to determine the tLim, t@VT2, and t@90%V̇O2peak tests. Blood lactate concentration ([La−]) was analyzed, and rate of perceived exertion (RPE) was recorded. The tests were conducted using a breath-by-breath apparatus connected to a snorkel for pulmonary gas sampling, with pacing controlled by an underwater visual pacer. V̇O2peak (55.2 ± 5.6 ml·kg·min−1) was only reached in CT (100.7 ± 3.1 %V̇O2peak). In addition, high V̇O2 values were reached at IT100 (96.4 ± 4.2 %V̇O2peak). V̇O2peak was highly correlated with Peak-V̇O2 during CT (r = 0.95, p < 0.01) and IT100 (r = 0.91, p < 0.01). Compared with CT, the IT100 presented significantly higher values for tLim (1,013.6 ± 496.6 vs. 256.2 ± 60.3 s), distance (1,277.3 ± 638.1 vs. 315.9 ± 63.3 m), t@VT2 (448.1 ± 211.1 vs. 144.1 ± 78.8 s), and t@90%V̇O2peak (321.9 ± 208.7 vs. 127.5 ± 77.1 s). V̇O2K time constants (IT100: 25.9 ± 9.4 vs. CT: 26.5 ± 7.5 s) were correlated between tests (r = 0.76, p < 0.01). Between CT and IT100, tLim were not related, and RPE (8.9 ± 0.9 vs. 9.4 ± 0.8) and [La−] (7.8 ± 2.7 vs. 7.8 ± 2.8 mmol·l−1) did not differ between tests. MAV is suitable for planning swimming intensities requiring V̇O2peak rates, whatever the exercise schedule (continuous or intermittent). Therefore, the results suggest IT100 as a preferable training schedule rather than the CT for aerobic capacity training since IT100 presented a significantly higher tLim, t@VT2, and t@90%V̇O2peak (∼757, ∼304, and ∼194 s more, respectively), without differing regards to [La−] and RPE. The V̇O2K seemed not to influence tLim and times spent near V̇O2peak in both workout modes.